Causes of severe visual impairment and blindness in schools for visually handicapped children in Iran. Issue 5 (15th April 2005) - Mirdehghan, S A; Dehghan, M H; Mohammadpour, M; Heidari, K; Khosravi, M
Abstract : Aims: This survey was conducted on children in schools for the blind in Tehran (from 2002 to 2003) to determine the causes of severe visual impairment and blindness and to identify preventable and treatable conditions. Methods: The study was performed on 362 students at different grades in three schools for the blind. Patient sex, age, family history of blindness or low vision, visual acuity, causes of blindness, and treatable and preventable conditions were studied. Results: Of the 362 cases, 210 (58%) were boys and 152 (42%) were girls. Mean age was 13.5 (SD 4) years. Severe visual loss was seen in 80.9%. Retinal diseases were the most common cause for low vision (51%); cataract, optic nerve atrophy, corneal and anterior segment diseases, glaucoma, anophthalmia, and globe malformations were other major causes of blindness. Treatable aetiologies and positive family history of blindness were seen in 25.7% and 36% of the patients, respectively. The incidence of preventable diseases, excluding familial disorders, was low. Conclusion: In addition to the prevention and treatment of some conditions, premarital genetic counselling and family planning control in families with inherited diseases could decrease the number of blind children in the future in Iran.